APPLICATION PROBLEM-SOLVING LEARNING MODEL TO IMPROVE SCIENCE LEARNING OUTCOMES IN STUDENTS CLASS IV ELEMENTARY SCHOOL GMIM 7 TOMOHON - Manggribeth, Stacy N.; Rindengan, Mersty; Palendeng, Francisca G.; Rorimpandey, Widdy H. F. (Journal of Educational Learning and Innovation (ELIa), 2023)
The research was conducted to improve science learning outcomes for fourth-grade students at GMIM 7 Tomohon Elementary School in the academic year 2022/2023, with a total of 33 students. This study used classroom action research (CAR) with four stages: planning, action implementation, observation, and reflection, which were applied in two cycles. In this study, observations and assessments were conducted by asking all students a series of written questions using Student Worksheets and Assessment Sheets. The data were analyzed using percentage calculations and the average learning outcomes achieved by the students. The initial data obtained showed that the students' science learning outcomes were 60%. The research results showed that the students' science learning outcomes experienced a significant improvement after implementing the problem-solving learning model. In Cycle I, there was an increase in learning outcomes to 70.15%. In Cycle II, the learning outcomes reached 90%. This research provides evidence of consistent improvement in the student's science learning outcomes from Cycle I to Cycle II. Based on the research findings and discussions, implementing the Problem-Solving learning model will improve the science learning outcomes of fourth-grade students at GMIM 7 Tomohon Elementary School. This research provides evidence of consistent improvement in the student's science learning outcomes from Cycle I to Cycle II. Based on the research findings and discussions, implementing the Problem-Solving learning model improves the science learning outcomes of fourth-grade students at GMIM 7 Tomohon Elementary School. This research provides evidence of consistent improvement in the student's science learning outcomes from Cycle I to Cycle II. Based on the research findings and discussions, implementing the Problem-Solving learning model improves the science learning outcomes of fourth-grade students at GMIM 7 Tomohon Elementary School.